Diagenesis versus hydrothermalism and fluid–rock interaction within the Tuscan Nappe of the Monte Amiata CO2‐rich geothermal area (Italy). Issue 2 (18th March 2013) - Gasparrini, M.; Ruggieri, G.; Brogi, A.
Abstract In southern Tuscany (central Italy), deep to shallow geothermal systems were active since the Pleistocene and comprise fluids carrying variable amounts of CO2. The Monte Amiata geothermal fields include two main reservoirs: a deep one located in the Palaeozoic metamorphic succession (1300–3000 m deep) belonging to the Tuscan metamorphic 'basement' and a shallow one hosted in the Mesozoic sedimentary succession (500–1000 m deep) belonging to the Tuscan Nappe. Multiple sets of calcite veins were investigated in some outcrops of the Tuscan Nappe succession exposed in the Monte Amiata area and surroundings. Two main fluid systems were characterized: the former related to combined diagenetic syn‐tectonic processes from highly saline fluids after interaction with the Late Triassic evaporites (Burano Fm) and the latter related to a fossil geothermal system, Pleistocene in age, fed by low‐salinity meteoric fluids, carrying CO2, radiogenic Sr and heavy O isotopes after interaction with the subsurface rocks. Comparison with the present‐day hydrothermal fluids allowed to sketch the thermal evolution of the system from past to present. Geochemical data proved that portions of the vein–host rocks were reset after interaction with CO2‐rich fluids circulating in the past. Consequently, textural and mineralogical changes are expected to have occurred with respect to the undisturbed rock masses. Understanding these modifications, their location and extension, is a prerequisite to construct (i) geochemical models addressed to the comprehension of the diagenesis induced in sediments after long‐term CO2 storage; and (ii) geological models applied to the prediction of rock heterogeneity distribution within the upper reservoirs, characterizing the shallow (500–1500 m) geothermal systems of southern Tuscany.